1992
DOI: 10.1021/ja00028a059
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale platinum(0) clusters in glassy carbon: synthesis, characterization, and uncommon catalytic activity

Abstract: Scheme 111 3 4 3 Ph-I, X = N3 or X OTMS 3 r' 3 b "-HX and Phl 3c

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 0 publications
0
34
1
Order By: Relevance
“…McCreery et al published a series of reports on the preparation of nanoscale Pt(0) clusters in GC by incorporating Pt in a GC precursor, followed by thermolysis at 600˚C. 29,30 The obtained film contained 2 -3 nm Pt nanoparticles, which show high electrocatalytic activity. Fujishima et al reported on electrochemically deposited Cu-or Ni-modified BDD films for electrocatalytically oxidizing sugars and amino acids.…”
Section: ·2 Sputtered Nano-film Electrodementioning
confidence: 99%
“…McCreery et al published a series of reports on the preparation of nanoscale Pt(0) clusters in GC by incorporating Pt in a GC precursor, followed by thermolysis at 600˚C. 29,30 The obtained film contained 2 -3 nm Pt nanoparticles, which show high electrocatalytic activity. Fujishima et al reported on electrochemically deposited Cu-or Ni-modified BDD films for electrocatalytically oxidizing sugars and amino acids.…”
Section: ·2 Sputtered Nano-film Electrodementioning
confidence: 99%
“…Several different carbon materials such as mesostructured carbon materials [1] , graphitic nanofibers [2] , mesocarbon microbeads [3] and hollow carbon spheres [4] were also reported as the supports of the Pt or Pt-based alloy catalysts [5,6] . However, major problems with porous carbon supports are as follows: Firstly, they lack chemical stability due to severe oxidation at higher positive potentials [7] . Secondly, self-agglomeration of the carbon particles within practical electrode structures limits the access of the fuel or the oxidant to the active sites of the electrocatalysts [8] .…”
mentioning
confidence: 99%
“…Nanostructures have received great attention recently due to their special optical, electronic, magnetic and chemical properties [1][2][3][4][5]. The most popular approach involves the synthesis of nanoparticles in situ within the block copolymer template by using preformed micelles of block copolymers containing metal precursors [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%